Higher serum testosterone concentration in older women is associated with insulin resistance, metabolic syndrome, and cardiovascular disease. - Patel, Shrita M; Ratcliffe, Sarah J; Reilly, Muredach P; Weinstein, Rachel; Bhasin, Shalender; Blackman, Marc R; Cauley, Jane A; Sutton-Tyrrell, Kim; Robbins, John; Fried, Linda P; Cappola, Anne R (J Clin Endocrinol Metab, 2009)
CONTEXT: Early postmenopausal women with higher testosterone (T) levels have increased insulin resistance (IR) and cardiovascular risk factors, but whether this translates into increased cardiovascular disease later in life is unknown. OBJECTIVE: The objective of the study was to determine whether higher T levels are associated with IR, the metabolic syndrome (MetSyn), and coronary heart disease (CHD) in elderly women. DESIGN: Total T and free T by equilibrium dialysis were measured using ultrasensitive assays in 344 women aged 65-98 yr enrolled in the Cardiovascular Health Study. Cross-sectional analyses were performed to examine the associations between total and free T and IR, MetSyn, and CHD. RESULTS: There was a stepwise increase in the homeostasis model assessment of insulin resistance with increasing total (P = 0.0.003) and free T (P = 0.02) level and a corresponding decrease in Quantitative Insulin Sensitivity Check Index (P < 0.001 and P = 0.002, respectively). In adjusted models, higher levels of both total and free T were strongly associated with abdominal obesity and high fasting glucose, the two MetSyn components most strongly linked to IR. After adjustment, women in the top quartile of total T levels had a 3-fold greater odds of MetSyn (odds ratio 3.15, 95% confidence interval 1.57-6.35) than those in the bottom quartile and a 3-fold greater odds of CHD (odds ratio 2.95, 95% confidence interval 1.2-7.3) than those in second quartile, whereas free T was not significantly associated with MetSyn or CHD. CONCLUSIONS: Higher levels of T are associated with IR, MetSyn, and CHD in elderly women. Whether T is a marker or mediator of cardiovascular disease in this population merits further investigation.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Cardiovascular Diseases; Coronary Disease; Female; Humans; Insulin; Insulin Resistance; Metabolic Syndrome; Odds Ratio; Radioimmunoassay; Socioeconomic Factors; Testosterone; Treatment Outcome